2013
DOI: 10.1292/jvms.13-0015
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Survey of Tick-Borne Protozoal Infection in Iriomote Cats and Tsushima Leopard Cats in Japan

Abstract: ABSTRACT. This epidemiological survey was conducted to determine the prevalence of Hepatozoon, Babesia and Theileria infection in the Iriomote cat (IC) and the Tsushima leopard cat (TLC). Blood samples from 43 ICs and 14 TLCs were collected between November 2002 and January 2012. Polymerase chain reaction and DNA sequencing analyses detected a Hepatozoon felis infection prevalence of 72.0% (31/43 cats) and 100% (14/14 cats) in ICs and TLCs, respectively. The degree of Hepatozoon parasitemia observed on blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 26 publications
2
25
2
Order By: Relevance
“…Our previous study showed a high prevalence of H. felis in ICs and TLCs, and the present study referred to those data indicating H. felis infection in host animals (Tateno et al, 2013a; Tables 2 and 3). We found that several tick species (H. longicornis, H. hystricis A. testudinarium, H. megaspinosa, I. tanuki, and H. campanulata) harbored Hepatozoon sp., all of which were confirmed to be H. felis.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our previous study showed a high prevalence of H. felis in ICs and TLCs, and the present study referred to those data indicating H. felis infection in host animals (Tateno et al, 2013a; Tables 2 and 3). We found that several tick species (H. longicornis, H. hystricis A. testudinarium, H. megaspinosa, I. tanuki, and H. campanulata) harbored Hepatozoon sp., all of which were confirmed to be H. felis.…”
Section: Discussionsupporting
confidence: 89%
“…In a previous study we were unable to detect the DNA of Babesia sp. in blood samples from both ICs and TLCs (Tateno et al, 2013a). Furthermore, a previous molecular epidemiological study failed to detect Babesia sp.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Since then, Hepatozoon spp. have been reported in domestic cats and various species of wild cats, and it is assumed that two or more species could be found in felids worldwide (Criado-Fornelio et al 2006; Kubo et al 2010; Pawar et al 2012; Baneth et al 2013; Tateno et al 2013). However, the parasite in cats was also referred to as Hepatozoon -like or Hepatozoon spp., without committing to a certain species, as the studies which described it were based only on morphological or genetic descriptions (Klopfer et al 1973; Baneth et al 1998; Perez et al 2004; Rubini et al 2006; Metzger et al 2008; Ortuño et al 2008; Salakij et al 2008).…”
Section: Introductionmentioning
confidence: 99%